Answer:
The Option 1 and Option 4 are correct.
Explanation:
The geometric sequence is:
-4,-6,-9,-27/2,-81/2,....
The Option 1 and Option 4 are correct.
f(1) = -4.
f(n) = 3/2 f(n-1)
Put n=2
f(2) = 3/2(f(1)
f(2) = 3/2(-4)
f(2) = -6
So, we get the series using this formula
Option 1 is correct.
Option 4 has formula
f(n) = -4 (3/2)^n-1
Put n= 1
f(1) = -4(3/2)^0
f(1) = -4
Put n = 2
f(2) = -4(3/2)^2-1
f(2) = -4(3/2)
f(2) = -6
Put n=3
f(3) = -4(3/2)^3-1
f(3) = -4(3/2)^2
f(3) = -4(9/4)
f(3)=-9
So we get the series, Hence Option 4 is correct.